Chronic Brucellosis in Japan - Kawakami, Naoki; Wakai, Yoko; Saito, Kazuhito; Imaoka, Koichi (Internal Medicine, 2019)
Human brucellosis, one of the most common zoonoses worldwide, rarely occurs in Japan, and only a few chronic cases have been reported. We herein report the case of a 39-year-old Japanese woman with chronic human brucellosis, considered a Brucella canis infection, that persisted for 19 years. Her medical history and fever pattern suggested chronic brucellosis, and the diagnosis was made based on the results of a serum tube agglutination test (SAT). After undergoing combination therapy with streptomycin and doxycycline, she achieved symptomatic relief and showed negative SAT results. Even in non-endemic areas, chronic brucellosis is an important differential diagnosis in patients with long-term persistent fatigue or a fever.